Ritual, performance and the senses - Bull, Michael 1952-; Mitchell, Jon P.; Taylor & Francis (Online service). (London New York Bloomsbury Academic, 2020)
"Ritual, Performance and the Senses is a unique and timely collection at the heart of which is an experiment in anthropological theory. It explores the possibility of developing a new anthropology of ritual by combining theoretical insights from three distinct domains of anthropological inquiry: cognitive/neuroanthropology, performance studies and the anthropology of the senses. These three areas of study are often considered, and indeed operate institutionally, as distinct academic sub-fields, and yet they share substantive objects of study, with their focus on experience, the body and the relationships between percept, concept and action. Bringing together scholars from each of these disciplines to consider the potential for drawing insights from each area to help to theorize ritual, this collection sheds new light on one of anthropology's most enduring research objects: by understanding ritual we understand processes at the very centre of human social life - of humanity itself. This will be invaluable reading for students and scholars of anthropology, cognitive science, performance studies and religious studies"-- Provided by publisher.
Introduction / Michael Bull and Jon P. Mitchell -- Ontology, mimesis and divine intervention : understanding Catholic visionaries / Jon P. Mitchell -- Ritual action shapes our brains : an essay in neuroanthropology / Robert Turner -- The importance of repetition : ritual as a support to mind / Greg Downey -- Place-making in the 'Holy of Holies' : The Church of the Holy Sepulchre, Jerusalem / Trevor H. J. Marchand -- The spaces and places of Ramnagar Ramlila / Richard Schechner -- 'Inner movement' between practices of mediation, martial arts and acting : a focused examination of affect, feeling, sensing and sensory attunement / Phillip B. Zarrilli -- Exploring the Andean sensory model : knowledge, memory and the experience of pilgrimage / Zoila Mendoza -- Sensation and transmission / David Howes.
Includes bibliographical references (pages 181-201) and index.
Keywords: Electronic books; Rites and ceremonies; Ritual; Neuroanthropology; Senses and sensation; Anthropology -- Methodology; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Sociology / General; ART / Performance